De novo genome assembly, annotation, and characterization of chemosensory genes in the camel ked (Hippobosca camelina) - Kebaso, F.; Diallo, S.; Kibet, C.; Hashim, S.; Makwatta, J.O.; Getahun, M.; Getange, D.; Domelevo Entfellner, Jean-Baka; Masiga, D. (BioMed Central, 2025)
Background: Hippobosca camelina (camel ked) is an obligate hematophagous ectoparasite that infests camels. Hematophagy inflicts painful bites leading to myiasis, anemia and pathogen transmission such as Candidatus Anaplasma camelii. A genome assembly for this biting flies is currently unavailable, limiting understanding of its genetics, including the chemosensory system.